2020
DOI: 10.1177/0890334420929993
|View full text |Cite
|
Sign up to set email alerts
|

Which Australian Women Do Not Exclusively Breastfeed to 6 Months, and why?

Abstract: Background Rates of exclusive breastfeeding in Australia lag behind international targets. Reasons for non-exclusive breastfeeding are poorly understood. Research aims To describe demographic profiles of participants reporting different feeding practices, and reasons for not exclusively breastfeeding to 6 months. Methods Demographics for 2888 mothers (5340 children) and reasons for 1879 mothers (3018 children) from the Mothers and Their Children’s Health Study (a sub-study of the Australian Longitudinal Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
(46 reference statements)
3
26
0
Order By: Relevance
“…This occurs for a multitude of reasons, reflecting breastfeeding difficulties and insufficient access to lactation support and postnatal care, as well as broader family and social support, access to paid maternity leave and social and cultural norms about infant feeding [3]. For some women, ceasing breastfeeding earlier than initially desired leaves them feeling stigmatised [4] and can be a source of shame, grief, guilt, distress and anxiety [5,6], contributing to a reduced sense of agency to achieve breastfeeding goals and poor psychological wellbeing [7,8] One of the most common reasons cited for early cessation of breastfeeding is perceived low or insufficient milk supply [9][10][11][12]. This should be managed initially by the provision of breastfeeding counselling and support [13], however, when concerns persist, substances known as galactagogues are often recommended [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This occurs for a multitude of reasons, reflecting breastfeeding difficulties and insufficient access to lactation support and postnatal care, as well as broader family and social support, access to paid maternity leave and social and cultural norms about infant feeding [3]. For some women, ceasing breastfeeding earlier than initially desired leaves them feeling stigmatised [4] and can be a source of shame, grief, guilt, distress and anxiety [5,6], contributing to a reduced sense of agency to achieve breastfeeding goals and poor psychological wellbeing [7,8] One of the most common reasons cited for early cessation of breastfeeding is perceived low or insufficient milk supply [9][10][11][12]. This should be managed initially by the provision of breastfeeding counselling and support [13], however, when concerns persist, substances known as galactagogues are often recommended [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the high proportion of mothers in our study with a university education (65•6 %), which may affect the generalisability of the findings. Duration of breast-feeding and first complementary food were retrospectively recalled; however, our previous work has found that breast-feeding to 6 months was recalled with more than 90 % accuracy when comparing measures in MatCH with measures in ALSWH, which were completed within 3 years of the child's birth (26) . First complementary food was not asked in ALSWH so we were unable to cross-check this variable; however, we did include a 'Can't remember' option in the list of potential first foods, and children where this option was selected were not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration of any or exclusive breast-feeding is associated with higher fruit and vegetable intake in childhood (19)(20)(21)(22)(23) , although associations with fruit intake are less consistent (19,24,25) . However, there is a great deal of variation in breast-feeding practices during the first 6 months, with some mothers exclusively breast-feeding, some supplementing with formula and/or complementary foods and some breast-feeding for less than 6 months or not at all (26) . Due to the focus in research on exclusive breast-feeding (20,23,25) , or failure to report on exclusive and mixed breast-feeding separately (19,22) , there is little information about whether these varying breast-feeding practices are associated with fruit and vegetable consumption in childhood.…”
mentioning
confidence: 99%
“…Rated as less important reasons are social ones, for instance, resuming work after maternity leave. Besides that, studies from other countries show that many women face problems when starting breastfeeding, resulting in early cessation of breastfeeding [17][18][19]. However, little is known about how women who are unable to breastfeed or are faced with breastfeeding problems perceive this situation.…”
Section: Introductionmentioning
confidence: 99%